Bathymetric ridges off Ras Spartel, western termination of the Strait of Gibraltar: Genetic considerations of singular shelf-margin morphological features - Pascal Le Roy; Francisco José Lobo; Ruth Durán; Debora Duarte; Léna Virat; Mohamed Sahabi; Marcaurelio Franzetti; Jacques Grall; Thierry Garlan (Geomorphology, 2026)

Conservation of the rare Astragalus tragacantha on the French Mediterranean coast: A case study of factors leading to transplantation success - Lucie Miché; Teddy Baumberger; Fatma Mirleau; Pascale Prudent; Marie Armange; Pascal Mirleau; Isabelle Laffont-Schwob; Thierry Tatoni; Lidwine Le Mire Pecheux; Antonin Dupin; Laureen Keller; Alex Baumel; et al. (Ecological Engineering, 2026)

Towards 0.1mm/yr stability over decades for measuring sea level using tide gauges together with GNSS-based instruments? - Pascal Bonnefond; Olivier Laurain; Pierre Exertier; Michel Calzas; Christine Drezen; Lionel Fichen; Antoine Guillot; Thierry Guinle; Nicolas Picot (Marine Geodesy, 2026)

First records of holothurian predation by the ocellated eagle ray (Aetobatus ocellatus) in Réunion island - Estelle Crochelet; Océane Desbonnes; Jean-Pascal Quod; Thierry Mulochau (Environmental Biology of Fishes, 2026)

Clinical spectrum of ICU-acquired invasive pulmonary aspergillosis according to SARS-CoV2 infection: a multicenter prospective cohort study - Florian Reizine; Mattéo Mauget; Nicolas Massart; Yannick Fedun; Anaïs Machut; Charles-Hervé Vacheron; Anne Savey; Arnaud Friggeri; Alain Lepape; Melissa Abbes; Abdelkrim Abdelmalek; Francoise Adema; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2026)

Petrochronology and genesis of granite-hosted rare metal (Ta, Nb, Li, Y + REE, Zr)-F-bearing mineral occurrences in the Cameroon Northern Domain of the Central African Orogenic Belt - Thierry Bineli Betsi; Eric Joseph Njee; Louise Marie Ngo Bidjeck Bondje; Eugene Pascal Binam Mandeng; Kirsten Drüppel; Aratz Beranoaguirre; Hubert Mvondo; Tebogo Kelepile; Elisabeth Eiche; Jochen Kolb; Charles Nkoumbou (Precambrian Research, 2026)

Analysis of Iguanodon bernissartensis teeth and bones using in-situ trace element, oxygen and strontium isotope composition: Implication for paleoecology, paleoenvironment and diagenesis - Sophie Decrée; Thierry Leduc; Pascal Godefroit; Etienne Deloule; Nolwenn Coint; Magdalena H. Huyskens; Eduardo T. Mansur; Vinciane Debaille; Jean-Marc Baele (Palaeogeography, Palaeoclimatology, Palaeoecology, 2026)

Corrigendum to “Identification of caseinophosphopeptides generated through in vitro gastro-intestinal digestion of Beaufort cheese” [Int. Dairy J. 129–134, 0958–6946] - Isabelle Adt; Coralie Dupas; Rachel Boutrou; Samia Dhahri; Nadia Oulahal; Claude Noel; Daniel Mollé; Thierry Jouvet; Pascal Degraeve (International Dairy Journal, 2026)

No impact of black-eye symptom on foraging behaviour and reproductive success of Northern gannets following highly pathogenic avian influenza - Aurore Ponchon; Pascal Provost; Alice Bernard; Thierry Boulinier; Mathilde Lejeune; Amélie Lescroël; Jérémy Tornos; David Grémillet (Biological Conservation, 2026)

A deletion in a photosynthesis-related gene (PpPSAK) determines the anthocyanin accumulation in the mesocarp of French blood-flesh peaches - Laure Heurtevin; Carole Confolent; Patrick Lambert; Sylvie Bureau; Thierry Pascal; Zhijun Shen; Bénédicte Quilot (Plant Science, 2025)

Spatio temporal dynamics of favourable habitats for Terminalia leiocarpa, a traditional plant used in ethnoveterinary medicine in Benin (West Africa) - Fabrice Jean Eudes Crédo Gahounga; Esaïe Tchetan; Sèdami Igor Armand Yevide; Thierry Dèhouégnon Houehanou; Pascal Abiodoun Olounlade; Joëlle Quetin-Leclercq; Adandé Berlamain Fandohan (Phytochemistry Letters, 2025)

Visitor impacts on social dynamics and space use in captive Western lowland gorillas (Gorilla gorilla gorilla) in a naturalistic zoo exhibit: A new methodological approach - Hugo Leroy; Calogero Montedoro; Jean-Pascal Guery; Thierry Hance (Applied Animal Behaviour Science, 2024)

Lithochemistry, and gold and sulphides chemistry from the Abiete-Toko Gold District in the NW edge Congo Craton, Nyong Complex (SW-Cameroon): Insights into the primary source of alluvial gold deposits and occurrence in the area - Eugène Pascal Binam Mandeng; Thierry Bineli Betsi; Rose Noël Ngo Belnoun; Louise Marie Ngo Bidjeck Bondjè; Yvan Demonstel Ntomb; Stella May Nome; Samira Ahidjo; Jacques Wassouo Wadjou; Lucien Dieudonné Bitom (Journal of Geochemical Exploration, 2024)

Climate forecast skill and teleconnections on seasonal time scales over Central Africa based on the North American Multi-Model Ensemble (NMME) - Roméo S. Tanessong; Thierry C. Fotso-Nguemo; Samuel Kaissassou; G. M. Guenang; A. J. Komkoua Mbienda; Lucie A. Djiotang Tchotchou; Armand F. Tchinda; Derbetini A. Vondou; Wilfried M. Pokam; Pascal M. Igri; Zéphirin D. Yepdo (Meteorology and Atmospheric Physics, 2024)

Effect of multi sourced compost on a rainfed olive tree grove in an arid land: Management practices to adapt to global climate change - Hayfa Rajhi; Anouar Bardi; Larbi Ajmi; Mariem Hazoug; Thierry Henry des Tureaux; Izharul Haq; Habib Bousnina; Mounir Abichou; Pascal Podwojewski (Journal of Arid Environments, 2023)

An LC-MS/MS method for the quantitative determination of 57 per- and polyfluoroalkyl substances at ng/kg levels in different food matrices - Xanthippe Theurillat; Claudia Mujahid; Bjorn Eriksen; Ashley Griffin; Andrew Savage; Thierry Delatour; Pascal Mottier (Food Additives & Contaminants: Part A, 2023)

Cover crop response to increased concentrations of copper in vineyard soils: Implications for copper phytoextraction - Pierre Eon; Thierry Robert; Jean-Pascal Goutouly; Violette Aurelle; Jean-Yves Cornu (Chemosphere, 2023)

Data quality control considerations in multivariate environmental monitoring: experience of the French coastal network SOMLIT - Elsa Breton; Nicolas Savoye; Peggy Rimmelin-Maury; Benoit Sautour; Eric Goberville; Arnaud Lheureux; Thierry Cariou; Sophie Ferreira; Hélène Agogué; Samir Alliouane; Fabien Aubert; Sébastien Aubin; et al. (Frontiers in Marine Science, 2023)
Introduction While crucial to ensuring the production of accurate and high-quality data—and to avoid erroneous conclusions—data quality control (QC) in environmental monitoring datasets is still poorly documented. Methods With a focus on annual inter-laboratory comparison (ILC) exercises performed in the context of the French coastal monitoring SOMLIT network, we share here a pragmatic approach to QC, which allows the calculation of systematic and random errors, measurement uncertainty, and individual performance. After an overview of the different QC actions applied to fulfill requirements for quality and competence, we report equipment, accommodation, design of the ILC exercises, and statistical methodology specially adapted to small environmental networks (<20 laboratories) and multivariate datasets. Finally, the expanded uncertainty of measurement for 20 environmental variables routinely measured by SOMLIT from discrete sampling—including Essential Ocean Variables—is provided. Results, Discussion, Conclusion The examination of the temporal variations (2001–2021) in the repeatability, reproducibility, and trueness of the SOMLIT network over time confirms the essential role of ILC exercises as a tool for the continuous improvement of data quality in environmental monitoring datasets.

Confirmation of the full conversion of ethylene oxide to 2-chloroethanol in fumigated foodstuffs: possible implications for risk assessment - Thomas Bessaire; Bjorn Eriksen; Stephanie Laborie; Claudia Mujahid; Pascal Mottier; Thierry Delatour; Alexandre Panchaud; Richard H. Stadler; Thomas Stroheker (Food Additives & Contaminants: Part A, 2023)

Trajectories of nutrients concentrations and ratios in the French coastal ecosystems: 20 years of changes in relation with large-scale and local drivers - Arnaud Lheureux; Valérie David; Yolanda Del Amo; Dominique Soudant; Isabelle Auby; Yann Bozec; Pascal Conan; Florian Ganthy; Gérald Grégori; Alain Lefebvre; Aude Leynart; Peggy Rimmelin-Maury; et al. (Science of The Total Environment, 2023)

Impact of bacterial strain acquisition in the lung of patients with COPD: the AERIS study - Lucio Malvisi; Aparna Yarraguntla; Marie-Cécile Mortier; Karen Osman; David W. Cleary; Béatrice Sente; Thierry G. Pascal; Vincent Weynants; Stuart C. Clarke; Laura Taddei; Tom M. A. Wilkinson; Jeanne-Marie Devaster; et al. (Infectious Diseases, 2022)

Rapid and Reliable Data Treatment for the Control of Food Chemical Contaminants by LC-HRMS - Benoît M. Carreres; Thomas Bessaire; Aurélien Desmarchelier; Pascal Mottier; Thierry Delatour (Food Additives & Contaminants: Part A, 2022)

Validating a New GNSS-Based Sea Level Instrument (CalNaGeo) at Senetosa Cape - Pascal Bonnefond; Olivier. Laurain; Pierre Exertier; Michel Calzas; Thierry Guinle; Nicolas Picot (Marine Geodesy, 2022)

Analysis of ethylene oxide in ice creams manufactured with contaminated carob bean gum (E410) - Thomas Bessaire; Thomas Stroheker; Bjorn Eriksen; Claudia Mujahid; Yves-Alexis Hammel; Jesus Varela; Thierry Delatour; Alexandre Panchaud; Pascal Mottier; Richard H. Stadler (Food Additives & Contaminants: Part A, 2021)

Seasonal and Interannual Variability of the CO2 System in the Eastern Mediterranean Sea: A Case Study in the North Western Levantine Basin - Cathy Wimart-Rousseau; Thibaut Wagener; Marta Álvarez; Thierry Moutin; Marine Fourrier; Laurent Coppola; Laure Niclas-Chirurgien; Patrick Raimbault; Fabrizio D’Ortenzio; Xavier Durrieu de Madron; Vincent Taillandier; Franck Dumas; et al. (Frontiers in Marine Science, 2021)
The seasonal variability of the carbonate system in the eastern Mediterranean Sea (EMed) was investigated based on discrete total alkalinity (A T ), total dissolved inorganic carbon (C T ), and pH measurements collected during three cruises around Crete between June 2018 and March 2019. This study presents a detailed description of this new carbonate chemistry dataset in the eastern Mediterranean Sea. We show that the North Western Levantine Basin (NWLB) is unique in terms of range of A T variation vs. C T variation in the upper water column over an annual cycle. The reasons for this singularity of the NWLB can be explained by the interplay between strong evaporation and the concomitant consumption of C T by autotrophic processes. The high range of A T variations, combined to temperature changes, has a strong impact on the variability of the seawater p CO 2 ( p CO 2 S W ). Based on Argo float data, an entire annual cycle for p CO 2 S W in the NWLB has been reconstructed in order to estimate the temporal sequence of the potential “source” and “sink” of atmospheric CO 2 . By combining this dataset with previous observations in the NWLB, this study shows a significant ocean acidification and a decrease in the oceanic surface pH T 25 of −0.0024 ± 0.0004 pH T 25 units.a –1 . The changes in the carbonate system are driven by the increase of atmospheric CO 2 but also by unexplained temporal changes in the surface A T content. If we consider that the EMed will, in the future, encounter longer, more intense and warmer summer seasons, this study proposes some perspectives on the carbonate system functioning of the “future” EMed.

A Marine Biodiversity Observation Network for Genetic Monitoring of Hard-Bottom Communities (ARMS-MBON) - Matthias Obst; Katrina Exter; A. Louise Allcock; Christos Arvanitidis; Alizz Axberg; Maria Bustamante; Ibon Cancio; Diego Carreira-Flores; Eva Chatzinikolaou; Giorgos Chatzigeorgiou; Nathan Chrismas; Melody S. Clark; et al. (Frontiers in Marine Science, 2020)
Marine hard-bottom communities are undergoing severe change under the influence of multiple drivers, notably climate change, extraction of natural resources, pollution and eutrophication, habitat degradation, and invasive species. Monitoring marine biodiversity in such habitats is, however, challenging as it typically involves expensive, non-standardized, and often destructive sampling methods that limit its scalability. Differences in monitoring approaches furthermore hinders inter-comparison among monitoring programs. Here, we announce a Marine Biodiversity Observation Network (MBON) consisting of Autonomous Reef Monitoring Structures (ARMS) with the aim to assess the status and changes in benthic fauna with genomic-based methods, notably DNA metabarcoding, in combination with image-based identifications. This article presents the results of a 30-month pilot phase in which we established an operational and geographically expansive ARMS-MBON. The network currently consists of 20 observatories distributed across European coastal waters and the polar regions, in which 134 ARMS have been deployed to date. Sampling takes place annually, either as short-term deployments during the summer or as long-term deployments starting in spring. The pilot phase was used to establish a common set of standards for field sampling, genetic analysis, data management, and legal compliance, which are presented here. We also tested the potential of ARMS for combining genetic and image-based identification methods in comparative studies of benthic diversity, as well as for detecting non-indigenous species. Results show that ARMS are suitable for monitoring hard-bottom environments as they provide genetic data that can be continuously enriched, re-analyzed, and integrated with conventional data to document benthic community composition and detect non-indigenous species. Finally, we provide guidelines to expand the network and present a sustainability plan as part of the European Marine Biological Resource Centre ( www.embrc.eu ).

Satellite and In Situ Monitoring of Chl-a, Turbidity, and Total Suspended Matter in Coastal Waters: Experience of the Year 2017 along the French Coasts - Francis Gohin; Philippe Bryère; Alain Lefebvre; Pierre-Guy Sauriau; Nicolas Savoye; Vincent Vantrepotte; Yann Bozec; Thierry Cariou; Pascal Conan; Sylvain Coudray; Gaelle Courtay; Sylvaine Françoise; et al. (Journal of Marine Science and Engineering, 2020)
The consistency of satellite and in situ time series of Chlorophyll-a (Chl-a), Turbidity and Total Suspended Matters (TSM) was investigated at 17 coastal stations throughout the year 2017. These stations covered different water types, from relatively clear waters in the Mediterranean Sea to moderately turbid regions in the Bay of Biscay and the southern bight of the North-Sea. Satellite retrievals were derived from MODIS/AQUA, VIIRS/NPP and OLCI-A/Sentinel-3 spectral reflectance. In situ data were obtained from the coastal phytoplankton networks SOMLIT (CNRS), REPHY (Ifremer) and associated networks. Satellite and in situ retrievals of the year 2017 were compared to the historical seasonal cycles and percentiles, 10 and 90, observed in situ. Regarding the sampling frequency in the Mediterranean Sea, a weekly in situ sampling allowed all major peaks in Chl-a caught from space to be recorded at sea, and, conversely, all in situ peaks were observed from space in a frequently cloud-free atmosphere. In waters of the Eastern English Channel, lower levels of Chl-a were observed, both in situ and from space, compared to the historical averages. However, despite a good overall agreement for low to moderate biomass, the satellite method, based on blue and green wavelengths, tends to provide elevated and variable Chl-a in a high biomass environment. Satellite-derived TSM and Turbidity were quite consistent with in situ measurements. Moreover, satellite retrievals of the water clarity parameters often showed a lower range of variability than their in situ counterparts did, being less scattered above and under the seasonal curves of percentiles 10 and 90.

Correction to: Persistence of High In Vivo Efficacy and Safety of Artesunate–Amodiaquine and Artemether–Lumefantrine as the First- and Second-Line Treatments for Uncomplicated Plasmodium falciparum Malaria 10 Years After Their Implementation in Gabon - Jacques M. Ndong Ngomo; Guy J. Ondzagha Megnie; Bridy Moutombi Ditombi; Jeanne V. Koumba Lengongo; Noé P. M’Bondoukwé; Christelle L. Offouga; Denise P. Mawili-Mboumba; Jean B. Lekana-Douki; Pascal Ringwald; Thierry Fandeur; Marielle K. Bouyou-Akotet (Acta Parasitologica, 2019)

Persistence of High In Vivo Efficacy and Safety of Artesunate–Amodiaquine and Artemether–Lumefantrine as the First- and Second-Line Treatments for Uncomplicated Plasmodium falciparum Malaria 10 Years After Their Implementation in Gabon - Jacques M. Ndong Ngomo; Guy J. Ondzagha Megnie; Bridy Moutombi Ditombi; Jeanne V. Koumba Lengongo; Noé P. M’Bondoukwé; Christelle L. Offouga; Denise P. Mawili-Mboumba; Jean B. Lekana-Douki; Pascal Ringwald; Thierry Fandeur; Marielle K. Bouyou-Akotet (Acta Parasitologica, 2019)
Purpose Artesunate–amodiaquine (AS–AQ) and artemether–lumefantrine (AL) have been widely used for the treatment of uncomplicated Plasmodium falciparum malaria since 2005 in Gabon. Since 2011, a rebound of malaria morbidity has been observed in this country, while no survey evaluating ACT efficacy was performed. During the same period, parasite resistance against artemisinin has been reported in Asia. The aim of this study was to assess the efficacy and tolerability of these two drugs in two sentinel sites of Gabon 10 years after their implementation. Methods Children aged from 12 to 144 months with uncomplicated malaria were recruited at the Regional Hospital of Melen, Libreville and in the Urban Health Center of Franceville between March 2014 and September 2015. The therapeutic efficacy was evaluated according to the WHO 2008 protocol of 28-day follow-up and PCR-uncorrected/corrected treatment outcomes were assessed. Results One hundred and eighty-five children (98 ASAQ and 89 AL) were followed up until day 28. The PCR-corrected ACPR was 98.9% for AS–AQ and 96.4% for AL. Late therapeutic failure rate was 3.6% and 1.1% for AL and AS–AQ, respectively ( p = 0.2). Adverse events and serious adverse events were rarely observed with both treatments. Conclusion AS–AQ and AL are still efficacious and well-tolerated for the treatment of uncomplicated malaria in Gabonese children.

Clove based cropping systems on the east coast of Madagascar: how history leaves its mark on the landscape - Natacha Arimalala; Eric Penot; Thierry Michels; Vonjison Rakotoarimanana; Isabelle Michel; Harisoa Ravaomanalina; Edmond Roger; Michel Jahiel; Jean-Michel Leong Pock Tsy; Pascal Danthu (Agroforestry Systems, 2019)

Neuroprotective effect of grape seed extract on brain ischemia: a proteomic approach - Safwen Kadri; Mohamed El Ayed; Pascal Cosette; Thierry Jouenne; Salem Elkhaoui; Sami Zekri; Ferid Limam; Ezzedine Aouani; Meherzia Mokni (Metabolic Brain Disease, 2019)

Long-term ecological observatories needed to understand ecohydrological systems in the Anthropocene: a catchment-scale case study in Brittany, France - Zahra Thomas; Pauline Rousseau-Gueutin; Benjamin W. Abbott; Tamara Kolbe; Hugo Le Lay; Jean Marçais; François Rouault; Christophe Petton; Pascal Pichelin; Geneviève Le Hennaff; Hervé Squividant; Thierry Labasque; et al. (Regional Environmental Change, 2019)

Comparison of metabolic profiles and bioactivities of the leaves of three edible Congolese Hibiscus species - Paulin Mutwale Kapepula; Nadege Kabamba Ngombe; Pascal Tshisekedi Tshibangu; César Tsumbu; Thierry Franck; Ange Mouithys-Mickalad; Dieudonné Mumba; Désiré Tshala-Katumbay; Didier Serteyn; Monique Tits; Luc Angenot; Pascal Dibungi T. Kalenda; et al. (Natural Product Research, 2017)

Nest design in a changing world: Great tit Parus major nests from a Mediterranean city environment as a case study - Marcel M. Lambrechts; Anne Charmantier; Virginie Demeyrier; Annick Lucas; Samuel Perret; Matthieu Abouladzé; Michel Bonnet; Coline Canonne; Virginie Faucon; Stéphanie Grosset; Gaëlle le Prado; Frédéric Lidon; et al. (Urban Ecosystems, 2017)

Antioxidant potentiality of three herbal teas consumed in Bandundu rural areas of Congo - Paulin Mutwale Kapepula; Patricia Mbombo Mungitshi; Thierry Franck; Ange Mouithys-Mickalad; Dieudonné Mumba Ngoyi; Pascal Dibungi T. Kalenda; Nadege Kabamba Ngombe; Didier Serteyn; Monique Tits; Michel Frédérich; Jean-Jacques Tamfum Muyembe (Natural Product Research, 2017)

Mapping of new resistance (Vr2, Rm1) and ornamental (Di2, pl) Mendelian trait loci in peach - Thierry Pascal; Romain Aberlenc; Carole Confolent; Mathilde Hoerter; Elodie Lecerf; Christophe Tuéro; Patrick Lambert (Euphytica, 2017)

Identifying SNP markers tightly associated with six major genes in peach [Prunus persica (L.) Batsch] using a high-density SNP array with an objective of marker-assisted selection (MAS) - Patrick Lambert; Jose Antonio Campoy; Igor Pacheco; Jehan-Baptiste Mauroux; Cassia Da Silva Linge; Diego Micheletti; Daniele Bassi; Laura Rossini; Elisabeth Dirlewanger; Thierry Pascal; Michela Troggio; Maria Jose Aranzana; et al. (Tree Genetics & Genomes, 2016)

Influence of bottom trawling on sediment resuspension in the ‘Grande-Vasière’ area (Bay of Biscay, France) - Baptiste Mengual; Florence Cayocca; Pierre Le Hir; Robin Draye; Pascal Laffargue; Benoit Vincent; Thierry Garlan (Ocean Dynamics, 2016)

Proteomics dedicated to biofilmology: What have we learned from a decade of research? - Arbia Khemiri; Thierry Jouenne; Pascal Cosette (Medical Microbiology and Immunology, 2016)

Characterization of endophytic Bacillus strains from tomato plants (Lycopersicon esculentum) displaying antifungal activity against Botrytis cinerea Pers - Asma Kefi; Imen Ben Slimene; Ines Karkouch; Christophe Rihouey; Sana Azaeiz; Marwa Bejaoui; Rania Belaid; Pascal Cosette; Thierry Jouenne; Ferid Limam (World Journal of Microbiology and Biotechnology, 2015)

Quantitative determination of sodium monofluoroacetate “1080” in infant formulas and dairy products by isotope dilution LC-MS/MS - Thomas Bessaire; Adrienne Tarres; Alexandre Goyon; Pascal Mottier; Mathieu Dubois; Wan Ping Tan; Thierry Delatour (Food Additives & Contaminants: Part A, 2015)

Nutrient ratios and the complex structure of phytoplankton communities in a highly turbid estuary of Southeast Asia - Thuoc Van Chu; Jean-Pascal Torréton; Xavier Mari; Huyen Minh Thi Nguyen; Kha Thi Pham; Thu The Pham; Thierry Bouvier; Yvan Bettarel; Olivier Pringault; Corinne Bouvier; Emma Rochelle-Newall (Environmental Monitoring and Assessment, 2014)

Developing core collections to optimize the management and the exploitation of diversity of the coffee Coffea canephora - Thierry Leroy; Fabien De Bellis; Hyacinthe Legnate; Pascal Musoli; Adrien Kalonji; Rey Gastón Loor Solórzano; Philippe Cubry (Genetica, 2014)

LC-MS/MS analytical procedure to quantify tris (nonylphenyl)phosphite, as a source of the endocrine disruptors 4-nonylphenols, in food packaging materials - Pascal Mottier; Nancy Frank; Mathieu Dubois; Adrienne Tarres; Thomas Bessaire; Roman Romero; Thierry Delatour (Food Additives & Contaminants: Part A, 2014)

Characterization and genetic mapping of a new blood-flesh trait controlled by the single dominant locus DBF in peach - Zhijun Shen; Carole Confolent; Patrick Lambert; Jean-Luc Poëssel; Bénédicte Quilot-Turion; Mingliang Yu; Ruijuan Ma; Thierry Pascal (Tree Genetics & Genomes, 2013)

Inheritance of resistance to coffee wilt disease (Fusarium xylarioides Steyaert) in Robusta coffee (Coffea canephora Pierre) and breeding perspectives - Pascal C. Musoli; Christian Cilas; David Pot; Agnes Nabaggala; Saleh Nakendo; James Pande; André Charrier; Thierry Leroy; Daniel Bieysse (Tree Genetics & Genomes, 2013)

Nest-box size influences where secondary-cavity exploiters roost and nest: a choice experiment - Marcel M. Lambrechts; Matthieu Abouladzé; Michel Bonnet; Virginie Demeyrier; Claire Doutrelant; Virginie Faucon; Gaëlle le Prado; Frédéric Lidon; Thierry Noell; Pascal Pagano; Philippe Perret; Stéphane Pouplard; et al. (Journal of Ornithology, 2013)

Variations in genomic DNA methylation during the long-term in vitro proliferation of oil palm embryogenic suspension cultures - Alain Rival; Pascal Ilbert; Axel Labeyrie; Esperanza Torres; Sylvie Doulbeau; Aline Personne; Stéphane Dussert; Thierry Beulé; Tristan Durand-Gasselin; James W. Tregear; Estelle Jaligot (Plant Cell Reports, 2013)

Pluri-annual study of the reproduction of two Mediterranean Oscarella species (Porifera, Homoscleromorpha): cycle, sex-ratio, reproductive effort and phenology - Alexander V. Ereskovsky; Maude Dubois; Julijana Ivanišević; Eve Gazave; Pascal Lapebie; Daria Tokina; Thierry Pérez (Marine Biology, 2013)

Global analysis of Coffea canephora Pierre ex Froehner (Rubiaceae) from the Guineo-Congolese region reveals impacts from climatic refuges and migration effects - Philippe Cubry; Fabien De Bellis; David Pot; Pascal Musoli; Thierry Leroy (Genetic Resources and Crop Evolution, 2013)

Recovery of viable cells from rabbit skin biopsies after storage at −20°C for up to 10 days - Djamila Benkeddache; Pascal Bodinier; Thierry Joly; Mokrane Berchiche; Xavier Vignon (Cell and Tissue Banking, 2012)

A model for conductive faults with non-matching grids - Xavier Tunc; Isabelle Faille; Thierry Gallouët; Marie Christine Cacas; Pascal Havé (Computational Geosciences, 2012)

Mapping Rm2 gene conferring resistance to the green peach aphid (Myzus persicae Sulzer) in the peach cultivar “Rubira®” - Patrick Lambert; Thierry Pascal (Tree Genetics & Genomes, 2011)

Computing with bacterial constituents, cells and populations: from bioputing to bactoputing - Vic Norris; Abdallah Zemirline; Patrick Amar; Jean Nicolas Audinot; Pascal Ballet; Eshel Ben-Jacob; Gilles Bernot; Guillaume Beslon; Armelle Cabin; Eric Fanchon; Jean-Louis Giavitto; Nicolas Glade; et al. (Theory in Biosciences, 2011)

Soil microbial diversity: an ISO standard for soil DNA extraction - Laurent Philippot; Cristina Abbate; Antonio Bispo; Thierry Chesnot; Sara Hallin; Philippe Lemanceau; Kristina Lindström; Pascal Pandard; Esperanza Romero; Michael Schloter; Pascal Simonet; Kornelia Smalla; et al. (Journal of Soils and Sediments, 2010)

Predictive modelling of seabed habitats: case study of subtidal kelp forests on the coast of Brittany, France - Vona Méléder; Jacques Populus; Brigitte Guillaumont; Thierry Perrot; Pascal Mouquet (Marine Biology, 2010)

Quantitative trait loci analysis of Plum pox virus resistance in Prunus davidiana P1908: new insights on the organization of genomic resistance regions - Manuel Rubio; Thierry Pascal; Alexandre Bachellez; Patrick Lambert (Tree Genetics & Genomes, 2010)

Generation of stable Xenopus laevis transgenic lines expressing a transgene controlled by weak promoters - Anne L’hostis-Guidet; Gaëlle Recher; Brigitte Guillet; Abdulrahim Al-Mohammad; Pascal Coumailleau; François Tiaho; Daniel Boujard; Thierry Madigou (Transgenic Research, 2009)

Coversand and Pleistocene palaeosols in the Landes region, southwestern France - Pascal Bertran; Giselle Allenet; Thierry Gé; Filipa Naughton; Philippe Poirier; Maria F. Sanchez Goñi (Journal of Quaternary Science, 2009)
New sections in the coversand of the Landes region, southwestern France, show at least two main depositional phases corresponding to the Upper Pleniglacial and the Lateglacial, which are separated by palaeosols. The lower palaeosol, a gleyic to histic cryosol overlying a net of sand wedges and dated to ca. 23 14 C ka BP, testifies to a short occurrence of permafrost. Impeded drainage due to the frozen subsoil is assumed to be the main factor involved in lowered aeolian transport and soil formation. Pollen analysis indicates a shrub tundra‐type environment. The overlying coversand unit is associated with small transverse ridges or sheet‐like deposits, and corresponds to the maximal extension of the sands, Upper Pleniglacial in age. An incipient podzol developed on the dunes under a boreal pine forest, and has been dated to 11.5–12 14 C ka BP, i.e. to the Allerød period. This has been buried by the second coversand unit during the Younger Dryas, typified by abundant denivation features and root imprints. Although preliminary, the chronology of sand deposition in the Landes region appears thus to be roughly similar to that found for the other European coversands, showing that all were the result of similar western European climatic changes, i.e. repeated episodes of increasing aridity related to the Upper Pleniglacial and the Younger Dryas episode. Copyright © 2008 John Wiley & Sons, Ltd.

Peroxiredoxin 2 is Involved in the Neuroprotective Effects of PACAP in Cultured Cerebellar Granule Neurons - Béatrice Botia; Damien Seyer; Aurélia Ravni; Magalie Bénard; Anthony Falluel-Morel; Pascal Cosette; Thierry Jouenne; Alain Fournier; Hubert Vaudry; Bruno J. Gonzalez; David Vaudry (Journal of Molecular Neuroscience, 2008)

Heme oxygenase-1 and interleukin-11 are overexpressed in stress-induced premature senescence of human WI-38 fibroblasts induced by tert-butylhydroperoxide and ethanol - Thierry Pascal; Florence Debacq-Chainiaux; Emmanuelle Boilan; Noëlle Ninane; Martine Raes; Olivier Toussaint (Biogerontology, 2007)

Fish community comparisons along environmental gradients in lakes of France and north‐east USA - Pascal Irz; François Michonneau; Thierry Oberdorff; Thomas R. Whittier; Nicolas Lamouroux; David Mouillot; Christine Argillier (Global Ecology and Biogeography, 2007)
Aim To assess whether eight traits of fish communities (species richness, three reproductive traits and four trophic traits) respond similarly to environmental gradients, and consequently display convergence between the lakes of France and north‐east USA (NEUSA). Location 75 French and 168 north‐east USA lakes. Methods The data encompass fish surveys, the assignment of species into reproductive and trophic guilds, and environmental variables characterizing the lakes and their catchments. The analytical procedure was adapted from the recommendations of Schluter (1986 ) [ Ecology , 67 , 1073–1085]. Results The comparison of the regional pools of lacustrine fishes indicated that NEUSA was about twice as speciose as France, mostly due to higher species turnover across lakes, although NEUSA lakes were consistently about 20% more speciose than French lakes for a given surface area. Warmer environments were consistently inhabited by a higher proportion of phytophilous and guarder species than were colder lakes. Hence there was convergence in community reproductive traits. Conversely, there was no evidence of convergence in the trophic structure of lacustrine fish communities between regions. Main conclusions The influence of temperature on the availability and quality of spawning substrates appears to be a major constraint on present‐day lacustrine fish communities. In parallel, phylogenetic constraints, past events such as the diversification of the North American fish fauna, and selective extinctions during Pleistocene glaciations and subsequent recolonizations contribute to explaining the dissimilarities between the communities of the two regions and differences in their relationship to the environment.

Protein expression in Escherichia coli S17-1 biofilms: impact of indole - Anthony Collet; Sébastien Vilain; Pascal Cosette; Guy Alain Junter; Thierry Jouenne; Robert S. Phillips; Patrick Di Martino (Antonie van Leeuwenhoek, 2006)

Native and introduced fish species richness in French lakes: local and regional influences - Pascal Irz; Christine Argillier; Thierry Oberdorff (Global Ecology and Biogeography, 2004)
Aim To analyse the importance of local and regional influences on the patterns of species richness in natural and man‐made lakes and to infer the impacts of human‐mediated introductions on these patterns. Location France. Methods Species occurrence data were gathered for 25 natural and 51 man‐made lakes. Analysis is based on regression models of local richness against their related regional richness and lake environmental variables. Results Local native richness was mostly controlled by the regional richness. Conversely, local total richness was mainly explained by local variables. These statements apply to both natural and man‐made lakes. Lacustrine systems displayed weak resistance to invaders. Main conclusions Species introductions have apparently contributed to saturate fish communities in these systems even if no clear negative effect on the survival of native species (i.e. species extinction) is detectable so far.

Stress-induced premature senescence: from biomarkers to likeliness of in vivo occurrence - Olivier Toussaint; José Remacle; Jean-François Dierick; Thierry Pascal; Christophe Frippiat; Véronique Royer; Joao Pedro Magalhacs; Stéphanie Zdanov; Florence Chainiaux (Biogerontology, 2002)

Characterization of a New Nepovirus Infecting Apricot in Southeastern France: Apricot Latent Ringspot Virus - Pascal Gentit; René-Pierre Delbos; Thierry Candresse; Jean Dunez (European Journal of Plant Pathology, 2001)

Stress-induced premature senescence as alternativetoxicological method for testing the long-term effectsof molecules under development in the industry - Olivier Toussaint; Patrick Dumont; Jean-François Dierick; Thierry Pascal; Christophe Frippiat; Florence Chainiaux; Joao-Pedro Magalhaes; François Eliaers; José Remacle (Biogerontology, 2000)

The biosynthesis and functionality of the cell-wall of lactic acid bacteria - Jean Delcour; Thierry Ferain; Marie Deghorain; Emmanuelle Palumbo; Pascal Hols (Antonie van Leeuwenhoek, 1999)

Early detection of staurosporine-induced apoptosis by comet and annexin V assays - Thierry Godard; Edwige Deslandes; Pierre Lebailly; Carole Vigreux; François Sichel; Jean-Michel Poul; Pascal Gauduchon (Histochemistry and Cell Biology, 1999)